Teachers' perceptions of history and history teaching in secondary schools - Yeo, Hwee Joo. (2008)
This study was taken to examine and analyze teachers’ perceptions of the meaning of History as wellas pedagogical practices in the teaching of History in secondary schools in Singapore. The study was undertaken with the objective to provide a better understanding to the perceptions and practices of trained History teachers.